Pengaruh Komunikasi dan Kompensasi Terhadap Kinerja Karyawan pada CU. Dosnitahi Pinangsori Kabupaten Tapanuli Tengah - Simon Horizon Mendrofa; Mhd. Shafwan Koto; Anna Basriyani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of communication and compensation on employee performance at CU. Dosnitahi Pinangsori, Central Tapanuli Regency. The research method used is a quantitative approach with descriptive and associative research types. The population in this study consisted of 66 employees, all of whom were used as samples through a saturated sampling technique. Data collection techniques included questionnaires, documentation, and literature study. Data analysis was conducted using validity and reliability tests, classical assumption tests, correlation analysis, coefficient of determination, multiple linear regression, and hypothesis testing (t-test and F-test). The results indicate that communication and compensation partially and simultaneously have a positive and significant effect on employee performance. The coefficient of determination of 62.9% shows that employee performance variation can be explained by communication and compensation, while the remaining is influenced by other variables outside this study.